2020
DOI: 10.1002/cncr.32652
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term mortality risks among patients with oropharynx cancer by human papillomavirus status

Abstract: Background There is substantial variation in head and neck cancer (HNC) mortality and competing mortality among patients with HNC. In this study, the authors characterize the causes and risks of short‐term mortality among patients with oropharynx cancer (OPC) and how these risks differ by human papillomavirus (HPV) status. Methods A custom Surveillance, Epidemiology, and End Results (SEER) data set with HPV status was used to identify 4930 patients with OPC who were diagnosed with nonmetastatic (M0) disease fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 22 publications
(46 reference statements)
0
7
0
1
Order By: Relevance
“…New studies have shown that patients with HPV-positive and HPV-negative oropharyngeal cancer have dramatically different rates of both head and neck carcinoma mortality and competing-cause mortality. Compared with HPV-positive patients, HPVnegative patients have a higher risk of two-year cumulative incidence of all-cause mortality and a lower risk of both head and neck carcinoma-specific mortality and competing-cause mortality (p < 0.0001) (Fullerton et al, 2020). Therefore, we believe that the HPV status is a critical determinant in oropharyngeal cancer.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…New studies have shown that patients with HPV-positive and HPV-negative oropharyngeal cancer have dramatically different rates of both head and neck carcinoma mortality and competing-cause mortality. Compared with HPV-positive patients, HPVnegative patients have a higher risk of two-year cumulative incidence of all-cause mortality and a lower risk of both head and neck carcinoma-specific mortality and competing-cause mortality (p < 0.0001) (Fullerton et al, 2020). Therefore, we believe that the HPV status is a critical determinant in oropharyngeal cancer.…”
Section: Discussionmentioning
confidence: 87%
“…Previous publications have focused in part on ceRNAs in laryngeal squamous cell carcinoma (LSCC) (Kong et al, 2019;Liu & Ye, 2019;Gao et al, 2019;Zhao et al, 2019;Sun et al, 2018;Feng et al, 2016), tongue squamous cell carcinoma (TSCC) (Sturgis & Cinciripini, 2007), and nasopharyngeal carcinoma (NPC) (Fullerton et al, 2020;Agrawal et al, 2011). These studies have identified differentially expressed RNAs by lncRNA and mRNA integrated microarrays of cancer tissue or by immunohistochemistry (Gao et al, 2019;Zhao et al, 2019;Sun et al, 2018;Feng et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…HPV status was tested using immunohistochemistry for p16 and/or polymerase chain reaction (PCR) or in situ hybridization (ISH)-based methods of pathologic specimens from either the primary oropharyngeal tumors or the corresponding cervical lymph node metastases. This HPV data set is reviewed by a SEER data-quality team to ensure accuracy ( 12 ). This study used a public de-identified SEER database and the institutional review board approval was waived.…”
Section: Methodsmentioning
confidence: 99%
“… 4 , 5 , 6 , 7 Both recurrence and subsequent malignancies are common, especially among HNC survivors with heavy alcohol and tobacco use. 8 Furthermore, HNC survivors may have pre‐existing comorbidities that require ongoing medical management and health promotion to reduce risk. With such complex ongoing health issues, HNC survivors require coordinated care beyond treatment completion.…”
Section: Introductionmentioning
confidence: 99%